2012
DOI: 10.1007/s10802-012-9677-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Risk Factors for Adolescent PTSD: Sources of Differential Exposure and Differential Vulnerability

Abstract: There are two types of risk factors for developing PTSD: factors that increase the likelihood of experiencing a potentially traumatizing event and factors that increase the likelihood of developing symptoms following such events. Using prospective data over a two-year period from a large, diverse sample of urban adolescents (n = 1242, Mean age = 13.5), the current study differentiates these two sources of risk for developing PTSD in response to violence exposure. Five domains of potential risk and protective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…A cross-lagged study of urban adolescents reported that PTSD symptoms predicted greater exposure to violent events during a two-year follow-up, and this event exposure mediated the relationship of initial PTSD symptoms with later severity (Milan et al, 2013). Similarly, a large 3-wave longitudinal study of urban adults found that PTSD symptoms predicted greater future non-assaultive trauma (e.g., serious illness), when taking into account baseline levels of PTSD and trauma exposure (Lowe, Walsh, Uddin, Galea, & Koenen, 2014).…”
Section: Reciprocal Influences Of Personality and Ptsdmentioning
confidence: 97%
See 1 more Smart Citation
“…A cross-lagged study of urban adolescents reported that PTSD symptoms predicted greater exposure to violent events during a two-year follow-up, and this event exposure mediated the relationship of initial PTSD symptoms with later severity (Milan et al, 2013). Similarly, a large 3-wave longitudinal study of urban adults found that PTSD symptoms predicted greater future non-assaultive trauma (e.g., serious illness), when taking into account baseline levels of PTSD and trauma exposure (Lowe, Walsh, Uddin, Galea, & Koenen, 2014).…”
Section: Reciprocal Influences Of Personality and Ptsdmentioning
confidence: 97%
“…In contrast, personality traits that measure the tendency to have a positive, outgoing disposition (e.g., extraversion/ positive emotionality) or behave in a controlled, cautious manner (e.g., conscientiousness/low disconstraint) show relatively weaker negative associations with PTSD (Pearson's rs = −0.25 and −0.27, respectively; Kotov et al, 2010). Understanding the relations of personality traits with PTSD is important, because personality may predict the course and severity of symptoms by affecting remission and relapse (Milan, Zona, Acker, & Turcios-Cotto, 2013;Stein, Jang, Taylor, Vernon, & Livesley, 2002). Although a number of studies have examined personality as a risk factor for the development of PTSD (e.g., Bramsen, Dirkzwager, & Van der Ploeg, 2000), the influence of personality on the course of symptoms remains poorly understood.…”
Section: Reciprocal Influences Of Personality and Ptsdmentioning
confidence: 99%
“…However, significant differences in the strength of the relationship between CVE and psychological distress were not found across African American adolescents in the United States, Jamaican immigrants in the United States, and Jamaican adolescents in Jamaica (Rosenthal & Wilson, ). A recent study with a large diverse urban sample (n = 1242, mean age 13.5 years), which included African Americans, Latinos, and Whites in the United States, found race/ethnicity (in addition to thought disorders and social problems) to be a significant predictor of PTSD after violence exposure (Milan, Zona, Acker, & Turcios, ).…”
mentioning
confidence: 99%
“…This categorical representation of age was used throughout analyses except where stated otherwise. Demographic factors potentially related to PTSS 16,25 (i.e., child age, household income, and race/ethnicity) and caregiver reporting (i.e., maternal education) were entered as covariates in Step 1 to examine the main and interacting effects of the variables of interest and rule out associations that may be due to confounding factors. The variable representing presence/absence of DSM-5 QTEs was added in Step 2 to evaluate the predictive contribution of Criterion A QTEs, and the variable representing the presence/absence of DSM-5 Non-QSEs was added in Step 3 to evaluate the incremental predictive contribution of non-qualifying stressful experiences on outcomes.…”
Section: Methodsmentioning
confidence: 99%